The Changes of Nerve Growth Factor Serum Levels After External Muscle Stimulation and The Correlation with Diabetic Neuropathy Symptom in Diabetic Peripheral Neuropathy - Dian Herdiansyah; Marina Annete Moeliono; Tertianto Prabowo (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Diabetic Peripheral neuropathy (DPN) is a common complication of diabetes mellitus. Recentstudies have demonstrated the involvement of Nerve growth factor (NGF) in the occurrence of DPN. TheDiabetes Mellitus was caused reduced the number and disruption of the function of the NGF. External MuscleStimulation (EMS) might be induced the NGF synthesis. The study objective has to found the effect of EMSon the NGF.Methods: Study design was before and after treatment without control on subjects with DPN. The bloodsample was taken before and after an intervention, as well as the Diabetic Neuropathy symptom (DNSym) andscore (DNSc). The EMS treated all of the participants within three times a week for four weeks.Results: There were 35 subjects were participated. Paired t-test showed a significant increase in NGF serumlevels and decrease both DNSym and DNSc with the difference value 12.64 ± 16.09 (p=0.000), 1.23 ± 0.82(p=0.000), 1.20 ± 0.85 (p=0.000). There was a significant negative correlation between NGF serum level withthe DNS- INA (r= -0.56; p=0.001) and the DNE-INA (r= -0.48; p=0.007).Conclusion: EMS treatment can increase serum NGF level. EMS has a strong correlation with a decrease inthe value of the DNS-INA and DNE-INA.Keywords: Diabetic Peripheral neuropathy, External Muscle Stimulation, Nerve Growth Factor.